Peran keluarga dalam memberikan dukungan terhadap pencapaian integritas diri pasien kanker payudara post Radikal Mastektomi - Anggraeni, Mekar Dwi; Ekowati, Wahyu (Jurusan Keperawatan FIKES UNSOED, 2010)
Background: Breast cancer is the second largest cancer in Indonesia. Patients with advancedstage breast cancer in particular, are generally filled with anger and depression at the thought of her illness. Family support is essential in patient care, one example is the situation after breast removal surgery (Radical Mastectomy). Methods: This study is a qualitative study with phenomenological approach that aims to explore the role of family in providing support to the achievement of self integrity breast cancer patients post Radical Mastectomy. Participants were selected by purposive sampling method which is a family of post Radical Mastectomy patients in Prof.Dr.Margono Soekarjo hospital. There are six partisipants join this research. Data collection techniques using in-depth interviews twice a further analysis of data using methods Collaizz's. Results: The research results show the role of family experience in providing support to the achievement of the integrity of the patient post Radical Mastectomy, covers six main themes: first, various assistance provided by the family, the less the support of the family as indicated by the husband who pays little attention and dishonesty diagnosis. Third, the family response to the condition and Fourth, the need at this moment perceived as a need for information about cancer and quality health services. Fifth, the various barriers in memendapatkan health services, and the Sixth, the various changes that occur in the family. Conclusion: The study provides implications of information regarding the role of family in providing social support to women post Radical Mastectomy and increase knowledge in providing nursing care to patients Breast Cancer Post Radical Mastectomy in Prof.Dr.Margono Soekarjo hospital, and help meet the diverse needs would social support to improve the quality of life of patients with breast cancer post radical mastectomy